The potential for a protective vaccine for rhinovirus infections. - Williams,GR; Kubajewska,I; Glanville,NS; Johnston,SL; Mclean,GR (Expert Review of Vaccines, 2016)
Rhinovirus (RV) infections impose a major disease burden as they cause around three out offour common colds and are responsible for the majority of acute exacerbations of chronicobstructive pulmonary disease (COPD) and asthma [1, 2]. RVs therefore are associated withan enormous economic cost in missed work or school and medical attention. Prophylacticvaccination against infection is arguably the most effective medical intervention everdeveloped, and has proven enormously effective in protecting against a large number ofdiseases. However, at the present time no effective vaccine exists for RVs. This is largelydue to the existence of 100 serotyped antigenically distinct RV strains - such variabilitymeans that a vaccine designed to elicit immune responses against a particular RV is unlikelyto be able to provide protection against the full range of virus subtypes successfully [3]. Infact, this phenomenon was observed as early as 1965 when immunising with formalininactivated whole RV and is confirmed by the knowledge that the immunity induced followingRV infection does not significantly protect from future infection by different RV serotypes [4].More sophisticated attempts at immunisation with multiple inactivated RV serotypes alsofailed to induce significant cross-serotype protection [5]. Thus, an effective cross-serotyperesponsive RV vaccine has remained elusive. The relatively recent description of a newclade of RV types (RV-C) has increased the number of identified strains/serotypes to ~160[6]. Perhaps the quest for a RV vaccine has been dismissed as too difficult or evenimpossible, but new developments suggest that it may be feasible to generate a significantbreadth of immune protection.